Low Resolution Limits and Inaccurate Algorithms Decrease Significantly the Value of Late Loss in Current Drug-Eluting Stent Trials - Johannes B. Dahm; Frank van Buuren (International Journal of Vascular Medicine)
Quantitative coronary and vascular angiography (QCA resp., QVA) remains the current gold standard for evaluation of restenosis. Late loss as one of the most commonly accepted parameters to highlight efficacy of the various devices has shown high correlation to clinical parameters but, surprisingly, has no impact on the evaluation of the remaining amount of restenostic tissue. The current clinical practice leads to unrealistic late loss calculations. Smaller late loss differences are usually not greater than the inherited resolution limits of QCA, which is especially the case in small differences between the various stents in the drug-eluting stent era. Late loss include additional systematic and random errors, due to the fact that measurements were taken at two different time points including the inherited resolution and calibration limits of QCA on two occasions. Due to the limited value of late loss in discriminating the small differences between the one and other DES, late lumen area loss and clearly defined calculation algorithms (e.g., MLD-relocation) should be used in future DES studies also to fulfill the more stringent regulatory requirements.